Cholestatic Injury Induced by Naproxen: A Rare Cause of NSAID-Induced Hepatotoxicity. Case Report. - Héctor M. Herrera-Martínez; Erika G. Salgado-Parra; Brenda N. Loza-Hernandez; Arturo Rodriguez-Guajardo; Byron I. Argoti-Mosquera (Annals of Hepatology)
Introduction and Objectives: Naproxen-induced liver injury is very rare (1-3 cases per 100,000 exposed individuals), typically occurring 1-6 weeks after ingestion¹. The damage can manifest with or without immunoallergic features and varying degrees of hepatocellular injury and cholestasis². We illustrate a case of a patient who developed cholestatic injury. Materials and Patients: A 51-year-old man, with the only relevant history being self-prescribed ingestion of 220 mg gel capsules of naproxen sodium two weeks prior for post-exercise muscle pain, presented on 04/05/24 with asthenia, vague abdominal pain in the right hypochondrium, jaundice, acholia, and dark urine. He sought medical emergency services two days later, where pronounced mucocutaneous jaundice, hepatomegaly, and hepatodynia were observed. Paraclinical tests showed hyperbilirubinemia: total bilirubin (TB) elevated due to direct bilirubin (DB), marked elevation of alkaline phosphatase (AP) and gamma-glutamyl transferase (GGT), and slight elevation of aspartate aminotransferase (AST) and alanine aminotransferase (ALT) (R factor = 2 mixed). Hepatic and biliary tract ultrasound reported diffuse increased hepatic echogenicity, ruling out biliary tract obstruction. Serological testing for hepatotropic viruses and TORCH screen were negative, as was the serological profile for autoantibodies. A percutaneous ultrasound-guided liver biopsy was performed; biopsies demonstrated intrahepatic cholestasis, minimal and focal lobular and portal interface hepatitis, macrovesicular steatosis; special stains negative for hemosiderin and glycogen deposits, fibrosis and copper-bound proteins; suggested of drug induced liver damage (Figure 1). Results: Drug-induced liver injury is a diagnosis of exclusion, only to be suspected when major causes of liver damage have been ruled out. Naproxen, a non-steroidal anti-inflammatory drug (NSAID) derived from propionic acid, has been reported to cause hepatotoxicity phenotypes of hepatocellular injury (acute hepatitis) and cholestasis through metabolic, immunoallergic and idiosyncratic mechanisms³. In this patient, the toxicity was non-dose-dependent, with an acute presentation characterized by a predominant elevation of cholestatic markers. Only supportive measures were provided, with close clinical and biochemical monitoring to identify early signs of liver dysfunction. The patient showed favorable evolution towards remission, characterized by symptomatic improvement and a progressive decrease in cholestatic markers within the first few days (Figure 2). After nine days of hospitalization, discharge was decided due to improvement, with a follow-up appointment for continued monitoring. Conclusions: In suspected naproxen-induced cholestatic injury, a liver biopsy is not required for diagnosis⁴ but is useful for understanding etiology, severity, extent, and prognosis. Discontinuing the causative agent is the first measure, and medical treatment should be directed solely by the clinical and biochemical evolution of the patient.